Gingival lesions diagnosed as pemphigus vulgaris in an adolescent. Case report - Navarro, Cláudia Maria [UNESP]; Sposto, M. R.; Onofre, Mirian Aparecida [UNESP]; Scully, C. (Amer Acad Periodontology, 1999)
Desquamative gingivitis (DG) is a fairly common disorder in which the gingivae show chronic desquamation. Originally considered to be related to hormonal changes at menopause, since many of the patients are middle-aged women, DG is now recognized to be mainly a manifestation of a number of disorders ranging from vesiculobullous diseases to adverse reactions to a variety of chemicals or allergens. Desquamative gingivitis can be an important early clinical manifestation of serious systemic diseases such as pemphigus vulgaris. The authors present a case that illustrates the importance of a specific diagnosis in patients with desquamative gingival lesions previously treated for 6 months as classical gingivitis. Gingival biopsy showed histologic patterns typical of pemphigus vulgaris. The patient was treated with systemic and topical corticosteroids in association with miconazole the patient is now under control with low-close systemic corticosteroids. Proper recognition of lesions in the oral mucosa leads, in several situations, to an early diagnosis of a systemic disease.
Keywords: gingivitis, desquamative; pemphigus; skin diseases, vesiculobullous; hypersensitivity, contact; hypersensitivity, chemical